Electroluminescence of thin-film CdTe solar cells and modules - Raguse, John Michael, author; Sites, James, advisor; Gelfand, Martin, committee member; Topič, Marko, committee member; Sampath, W. S., committee member; de la Venta, Jose, committee member (Colorado State University. Libraries, 2015)
Thin-film photovoltaics has the potential to be a major source of world electricity. Mitigation of non-uniformities in thin-film solar cells and modules may help improve photovoltaic conversion efficiencies. In this manuscript, a measurement technique is discussed in detail which has the capability of detecting such non-uniformities in a form useful for analysis. Thin-film solar cells emit radiation while operating at forward electrical bias, analogous to an LED, a phenomena known as electroluminescence (EL). This process relatively is inefficient for polycrystalline CdTe devices, on the order of 10⁻⁴%, as most of the energy is converted into heat, but still strong enough for many valuable measurements. A EL system was built at the Colorado State University Photovoltaics Laboratory to measure EL from CdTe cells and modules. EL intensity normalized to exposure time and injection current density has been found to correlate very well with the difference between ideal and measured open-circuit voltage from devices that include a GaAs cell, an AlGaAs LED, and several CdTe cells with variations in manufacturing. Furthermore, these data points were found to be in good agreement when overlaid with calibrated data from two additional sources. The magnitude of the inverse slope of the fit is in agreement with the thermal voltage and the intercept was found to have a value near unity, in agreement with theory. The expanded data set consists of devices made from one of seven different band gaps and spans eight decades of EQELED efficiencies. As expected, cells which exhibit major failure of light-dark J-V superposition did not follow trend of well-behaved cells. EL images of selected defects from CdTe cells and modules are discussed and images are shown to be highly sensitive to defects in devices, since the intensity depends exponentially on the cells' voltages. The EL technique has proven to be a useful high-throughput tool for screening of cells. In addition to EL images, other opto-electronics characterization techniques were used to analyze defects in cells and modules such as weak-diode areas, cell delineation near substrate edge, non-uniform chlorine passivation, holes in back contact, high-resistance foreign layer, high back-contact sheet resistance, a discontinuous P3 line scribe (intercell shunt) and shunt through a cell (intracell shunt). Although EL images are proficient at illustrating the location and severity of defects with potentially high spatial resolution and short measurement times, their ability to identify the cause of such defects is limited. EL in concert with Light-Beam-Induced Current (LBIC), however, makes for a powerful ensemble as LBIC can probe different film layers at arbitrary voltage bias conditions, albeit with increased measurement times and potentially reduced spatial resolution.
Keywords: characterization; photovoltaics; electroluminescence; CdTe